RESULTS SIMULTANEOUS OPERATIONS IN PATIENTS WITH ADRENAL TUMORS - Sakhiboev Dilshod Parpijalilovich (Western European Studies, 2025)
In the period from 2013 to 2015 the 2-clinic of Tashkent Medical Academy for examination and treatment were 46 patients with adrenal tumors. Simultaneous operations were performed in 6 patients, of whom 4 women and 2 men. A morphological study of adrenal tumors, we found: 2 - aldosteroma (33.3%), 1- pheochromocytoma (16.6%), 1 - adrenal cyst (16.6%), 2 - cortex adenoma (33.3%). Of these, 50% patients were with intsidentaloma (2 cortical adenoma and 1 adrenal cyst). Indications for simultaneous operations were a combination of adrenal tumors with cholelithiasis and umbilical hernia. At the same time in 4 (66.6%) patients simultaneously conducted operations - right-sided laparoscopic adrenalectomy, and laparoscopic cholecystectomy, in 1 patient (16.6%) - a left laparoscopic adrenalectomy and laparoscopic cholecystectomy and 1 (16.6%) patient’s after adrenalectomy surgery hernia repair is made to the type of allopath.
Keywords: tumor of adrenal glands; simultaneous operations; laparoscopic adrenalectomy